2019
DOI: 10.3390/microorganisms8010039
|View full text |Cite
|
Sign up to set email alerts
|

HHV-6A Infection and Systemic Sclerosis: Clues of a Possible Association

Abstract: Systemic sclerosis (SSc) is an autoimmune disease characterized by vasculopathy, excessive extracellular matrix deposition, and fibrosis of the skin and internal organs. Several infectious agents, including human herpesvirus-6 (HHV-6), have been suggested as possible triggering factors, but a direct association is still missing. We characterized 26 SSc patients for the presence of HHV-6 in tissues and blood, the anti-HHV-6 response, HLA-G plasma levels, and KIR typing. Given the prominent role of endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 66 publications
2
49
1
2
Order By: Relevance
“…The pattern of pro-fibrotic factors induced by HHV-6A in fibroblasts was similar but not completely superimposable with that observed in endothelial cells, where IL-4, TNFα, and MMP9 were similarly induced [ 15 ], but IL-5 was also increased, in contrast to what was detected in fibroblasts, suggesting that viral strategies depend, at least partly, on the cell type and microenvironment.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The pattern of pro-fibrotic factors induced by HHV-6A in fibroblasts was similar but not completely superimposable with that observed in endothelial cells, where IL-4, TNFα, and MMP9 were similarly induced [ 15 ], but IL-5 was also increased, in contrast to what was detected in fibroblasts, suggesting that viral strategies depend, at least partly, on the cell type and microenvironment.…”
Section: Discussionmentioning
confidence: 56%
“…Recent studies have confirmed the high prevalence of beta-herpesvirus infection in SSc subjects, testified by both presence of the viruses at the tissue and/or blood level and by the detection of a significantly higher immune response against HCMV and HHV-6 in SSc patients compared to controls [ 15 , 16 , 26 , 59 ]. Furthermore, HHV-6A was shown to be capable of inducing the expression of pro-fibrotic factors in endothelial cells [ 15 ], but no information are available about the ability of both HHV-6 and HCMV to induce the expression of fibrosis- and apoptosis-associated factors in human dermal fibroblasts, that are one of the main target cells of the disease.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations